Lack of nasal carriage of novel corona virus (HCoV‐EMC) in French Hajj pilgrims returning from the Hajj 2012, despite a high rate of respiratory symptoms. (2nd March 2013) - Gautret, P.; Charrel, R.; Belhouchat, K.; Drali, T.; Benkouiten, S.; Nougairede, A.; Zandotti, C.; Memish, Z. A.; al Masri, M.; Gaillard, C.; Brouqui, P.; Parola, P.; et al.
Abstract A cohort of 154 French Hajj pilgrims participating in the 2012 Hajj were systematically sampled with nasal swabs prior to returning to France, and screened for the novel HCoV‐EMC coronavirus by two real‐time RT‐PCR assays. Despite a high rate of respiratory symptoms (83.4%), including 41.0% influenza‐like illness, no case of HCoV‐EMC infection was detected. Despite the fact that zoonotic transmission was suspected in the first few cases, a recent family cluster in the Kingdom of Saudi Arabia suggests that the virus might show at least limited spread from person to person, which justifies continuing epidemiological surveillance.